Pixel detectors for diffraction‐limited storage rings. (1st September 2014) - Denes, Peter; Schmitt, Bernd
<x xml:space="preserve">Abstract</x> Dramatic advances in synchrotron radiation sources produce ever‐brighter beams of X‐rays, but those advances can only be used if there is a corresponding improvement in X‐ray detectors. With the advent of storage ring sources capable of being diffraction‐limited (down to a certain wavelength), advances in detector speed, dynamic range and functionality is required. While many of these improvements in detector capabilities are being pursued now, the orders‐of‐magnitude increases in brightness of diffraction‐limited storage ring sources will require challenging non‐incremental advances in detectors. This article summarizes the current state of the art, developments underway worldwide, and challenges that diffraction‐limited storage ring sources present for detectors.